(untitled) (European Journal of Pedagogical Initiatives and Educational Practices, 2024)
The rapid development of cloud technologies has brought transformative opportunities for library systems globally. Libraries, as hubs of information and learning, are increasingly adopting cloud-based solutions to enhance their service delivery, improve resource accessibility, and streamline operations. This paper explores the skills required for effectively utilizing cloud technologies in library settings. By analyzing current trends and practical applications, it identifies the technical, organizational, and interpersonal competencies necessary for librarians to harness the potential of cloud computing. Additionally, the study highlights challenges and best practices, offering a comprehensive framework for libraries aiming to integrate cloud technologies efficiently.